Analisis Risiko Pelaksanaan Work From Home Berbasis Iso31000 Bagi Para Pekerja Sosial Di Wilayah Kabupaten Jayapura - Andreas, Rudolf; Denny Tewu, Magit Les (Fakultas Ekonomi Universitas Gresik, 2023)
The purpose of this study was to identify and obtain information about the risks faced by social workers when working from home during the COVID-19 pandemic. The study used the bow tie analysis method to analyze all the risks and mitigation plans that these social workers will take in doing their daily work. Researchers also took qualitative and quantitative samples of 15 correspondents to take data on what risks they faced during work. Correspondents in this study are staff and tutors of child workers and educators at the Child Development Center in Jayapura Regency. The initials of each correspondent will be kept secret using codes R1, R2 and so on. As a result of this research, researchers will get a full picture of the risks and mitigation plans to support child labor to continue to work well and achieve the targets set by the organization